Biomarkers of Peripheral Nonperfusion in Retinal Venous Occlusions Using Optical Coherence Tomography Angiography - Cabral, Diogo (2019)
Purpose: To study the association between the assessment of central macular vascular layers by optical coherence tomography angiography (OCT-A) and peripheral nonperfusion evaluated by fluorescein angiography (FA) in patients with retinal venous occlusion (RVO). Methods: Retrospective review of RVO patients without macular edema. Patients underwent a comprehensive ophthalmic examination including FA, spectral-domain OCT, and OCT-A. Significant ischemia was defined as nonperfusion areas superior or equal to the equivalent of one retinal quadrant on FA. Vascular density (VD) and foveal avascular zone were measured using AngioAnalytics software. Fractal dimension (FD) and lacunarity (LAC) were computed using an algorithm designed by MATLAB (MathWorks, Natick, MA). These variables were used to build a model that translates their association with OCT-A parameters. Results: There were 48 eyes (48 patients) of which 19 had significant peripheral nonperfusion. Deep capillary plexus FD, VD, and LAC were associated with significant ischemia. In fact, regarding the association with this outcome, LAC alone had the highest area under the curve (AUC = 0.88) followed by FD (AUC = 0.85) and VD (AUC = 0.73). The multivariable model that included LAC and VD, adjusted by best-corrected visual acuity (BCVA) achieved the best performance for the identification of severe nonperfusion on wide-field FA (AUC = 0.93). Conclusions: The characteristics of the central macular deep capillary plexus on OCT-A may be associated with peripheral nonperfusion on FA, particularly the combination of LAC and vessel density after adjusting by BCVA. Translational Relevance: Fractal-based metrics applied to OCT-A may become a valuable marker of ischemia in RVO and help guide the clinical decision to perform invasive angiography.